THE COMPARISON OF THINK TALK WRITE AND THINK PAIR SHARE WITH TALKING STICK VIEWED FROM STUDENTS' INDEPENDENT LEARNING EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Doni Susanto; Mardiyana Mardiyana; Dewi Retno Sari Saputro (Proceedings Education and Language International Conference, 2017)
This research was a quasi-experimental research with 2×3 factorial design. It aimed to determine the learning model between Think Talk Write with Talking Stick (TTW-TS) and Think Pair Share with Talking Stick (TPS-TS) that gave the best achievement on mathematics subject viewed from students' independent learning. The population of this research were all of Junior High School students at the 8th grade in Ngawi Regency, East Java, Indonesia in academic year 2016/2017 which applied KTSP curriculum. The sample was taken by using stratified cluster random sampling. The data were collected by using methods of documentation, students' independent learning questionnaires, and mathematics achievement test. Data analysis technique used two ways analysis of variance (ANOVA) with unequal cell. According to the research findings, it could be concluded that: (1) students' mathematics achievement which were taught by using TTW-TS is as good as students' mathematics achievement which were taught by using TPS-TS in relation and function material, (2) mathematics achievement of students with high independent learning is better than students with medium and low independent learning, and mathematics achievement of students with medium independent learning is as good as students with low independent learning in relation and function material, (3) in each learning model, mathematics achievement of students with high independent learning is better than students with medium and low independent learning, and mathematics achievement of students with medium independent learning is as good as students with low independent learning in relation and function material (4) in each category of high and medium independent learning, student’s mathematics achievement which were taught by using TTW-TS is better than student’s mathematics achievement which were taught by using TPS-TS and in low independent learning student’s mathematics achievement which were taught by using TTW-TS is as good as student’s mathematics achievement which were taught by using TPS-TS in relation and function material. Keywords: Think talk write, think pair share, talking stick, independent learning, relation and function